Análise da sustentabilidade urbana por intermédio do estudo das condições de acessibilidade e mobilidade no corredor da Avenida Dom Pedro II, João Pessoa-PB - Oliveira, Juliana Xavier Andrade de (2022)
The increase in the urban population, the territorial extensions of cities, and the growth of private motorization are crucial factors for understanding the situation of (un)sustainable urban mobility in the cities. Given growing urbanization, high levels of individual motorization, and the dispersed cities. And the identified pattern regarding occupation and horizontal growth in the South-Southeast sector of João Pessoa, progressively taking distance from the city center and interfering with local urban transport. This research aims to evaluate the mobility and accessibility conditions along the axis of the corridor of Dom Pedro II Avenue, including the space of occupation and the land use in its area of direct influence (500 meters), and adjoining neighborhoods, through the application of the sustainable urban mobility indicators (SUMI). As the results revealed by the SUMI for the analyzed sample, there is a global value of 0,564, considered an intermediate value for sustainable mobility. However, the index calculation shows pathways to improve mobility since it allows an efficient perception of the evaluated factors, positively or negatively. It also highlights the need for intervention to improve the indicators of Urban Fragmentation; Urban density; Bicycle parking, and Urban Transport Systems domain as a whole. In addition, the city's growing report indicates that studies have been carried out (PAITT, TRANSCOL and PDU), and efforts were made to improve urban mobility, especially regarding the public transport system in the analyzed sample. However, this still seems to be the most critical issue.